Fulminant central nervous system varicella-zoster virus infection unexpectedly diagnosed by metagenomic next-generation sequencing in an HIV-infected patient: a case report - Mingxia Fang; Xing Weng; Liyun Chen; Yaling Chen; Yun Chi; Wei Chen; Zhiliang Hu (BMC Infectious Diseases, 2020)
Abstract Background Varicella-zoster virus (VZV) infection can be diagnosed clinically once classical rash occurs but the diagnosis is challenging when typical rash is absent. We reported a case of fulminant central nervous system (CNS) VZV infection in a human immunodeficiency virus (HIV)-infected patient without typical VZV-related rash. CNS VZV infection was unexpected identified by metagenomic next-generation sequencing (mNGS). Case presentation A 28-year-old HIV-infected patient presented with neurological symptoms for 3 days. The patient, who was not suspected of VZV infection at admission, quickly progressed to deep coma during the first 24 h of hospitalization. An unbiased mNGS was performed on DNA extract from 300 μL cerebrospinal fluid (CSF) with the BGISEQ-50 platform. The sequencing detection identified 97,248 (out of 38,561,967) sequence reads uniquely aligned to the VZV genome, and these reads covered a high percentage (99.91%) of the VZV. Presence of VZV DNA in CSF was further verified by VZV-specific polymerase chain reaction and Sanger sequencing. Altogether, those results confirmed CNS VZV infection. Conclusions This study suggests that mNGS may be a useful diagnostic tool for CNS VZV infection. As mNGS could identify all pathogens directly from CSF sample in a single run, it has the promise of strengthening our ability to diagnose CNS infections in HIV-infected patients.